PENATAAN STRUKTUR ORGANISASI DINAS KEPENDUDUKAN DAN PENCATATAN SIPIL KABUPATEN MINAHASA - TEWU, NEISSY; LENGKONG, FLORENCE; RARES, JOYCE JACINTA (Sam Ratulangi University, 2022)
The purpose of this study is to analyze the Organizational Structuring of the Minahasa RegencyPopulation and Civil Registration Service in response to Government Regulation Number 41 of 2007 as anurgency for the Regional Government in the Population and Civil Registration Service to collaborate intasks within the Government Organization. Descriptive qualitative research methods. The result of thisresearch is an analysis of the organizational structure of the population service and civil registration byresponding to Government Regulation Number 41 of 2007 which is analyzed using the theory of theRegional Apparatus Organization. The results obtained are that the analysis of the organizational structureof the Minahasa Regency Population and Civil Registration Office has been successfully implemented, butthere are still obstacles in doing existing work, stalling for work, not maximizing work and only prioritizingone's own interests compared to work.Keywords: Regional Government Organizational Structuring